Perceived Parenting and Basic Need Satisfaction among Portuguese Adolescents. (10th August 2015) - Cordeiro, Pedro; Paixão, Maria Paula; Lens, Willy
Abstract: We examined the psychometric properties of the Parenting Questionnaire in a sample of Portuguese high school students. Two measurement models were specified. Model 1m, f specifies a bi-dimensional structure of parental need-support and behavioral control. Model 2m, f proposes a tripartite structure of parental need-support, psychological control and behavioral control. Model 2m, f. best-fitted the data, being also supported in terms of convergent, discriminant validity. Regression results found the unique effect of autonomy-support (M2mr, b = .25 p < .001; M2fr, b = .14 p < .01), responsiveness-warmth (Model 2mr, b = .19, p < .001; Model 2fr, b = .13 p < .05) and behavior control on basic need-satisfaction (Model 2mr : b = .14 p < .05), but a non-significant effect of psychological control on need-frustration ( p > .05). Notably, psychological control predicted low need-satisfaction (M2mr : b = –.10) and moderated of the positive effect of parental need-support on need-satisfaction, M2mr : F (3, 367) = 11.62, p < .001. Psychological control and need-support also moderated the positive effect of behavior control on competence satisfaction, with parental need-support amplifying this effect and psychological control buffering it. Overall the findings support the substantive distinction between the parenting dimensions, suggesting that need-satisfaction is enhanced by need-supportive and behavioural control and undermined by psychological control.